A dimensionless parametric study for forced vibrations of foundation–soil systems. (June 2016) - Chen, Shi-Shuenn; Liao, Ke-Hung; Shi, Jun-Yang
Abstract: This paper studies the coupling responses for a foundation–soil system undergoing horizontal forces and rocking moments. A numerical program is developed to perform a dimensionless analysis for investigating the effects of dominant parameters on the foundation responses. Those dominant parameters include Poisson's ratios, thickness ratios, dimensionless frequencies, and mass ratios. The presented results show that the coupling between the horizontal and rotational response is much significant for massive foundations. The Poisson's ratio of soil limitedly influences the dynamic response along the direction of the force. The analytical solutions proposed may provide valuable insights to investigate machine foundation vibrations in practice.